Komparasi Enzim Kitinase dari Beauveria bassiana galur Lokal Sulawesi Selatan terhadap Mortalitas Ulat Grayak (Spodoptera litura) (The Comparation Chitinase Enzyme of Beauveria bassiana Local Strain South Sulawesi to Mortality Spodoptera litura) - Rachmawaty (Jurusan Biologi Universitas Negeri Makassar, 2009)
This study aims to determine the enzyme activity of chitinase B. bassiana strain found in South Sulawesi. Knowing the relationship between the activity of chitinase enzyme isolate-isolate B.bassiana strain in South Sulawesi with mortality grayak caterpillar (Spodoptera litura). This descriptive research by linking the enzyme activity of chitinase from Beauveria bassiana strain local South Sulawesi on mortality grayak caterpillar larvae (Spodoptera litura). Based on the research that has been done shows that the activity of the enzyme from South Sulawesi B.bassiana local strains showed differences in each isolate, isolates the origin Enrekang 7.15 units / ml, isolate origin Bantaeng 7.12 units / ml, 6.32 units of isolate origin Pinrang / mi and isolate the origin of Maros 6.2 units / ml. There is a relationship between enzyme activity with mortality rates of larvae of Spodoptera litura. The highest mortality is caused by the isolate origin Enrekang 86%, followed by the isolate origin Bantaeng 83%, 76% Pinrang origin isolates and isolate the origin of Maros 73%.